Bridging Design and Economics: A PSI Framework Analysis of Residency Matching Market Evolution - Yoram Reich; Eswaran Subrahmanian (She Ji: The Journal of Design, Economics and Innovation)
This paper addresses a divide: economics and design remain largely disconnected despite shared concerns about shaping products, services, and social systems. We propose that bridging design theory and practices—especially the Problem-Social-Institutional (PSI) framework—into market economics can aid the design of complex products and institutions. We illustrate this potential through an in-depth analysis of the evolution of US, Canadian, and British medical residency matching markets, which assign medical graduates to hospitals. Initially considered a purely optimal allocation problem, these markets repeatedly failed, stemming mainly from information asymmetry and shifting participant needs. With PSI, we show how changes in problem framing, stakeholder roles, and institutional structures can realign these markets toward stability and better outcomes. This transdisciplinary view positions market design as an iterative, evolving process, much like engineering a product or service. Our conclusions suggest that economists can benefit from design theories such as PSI and design practices such as prototyping, simulation, and stakeholder engagement. Further, we contend that design theorists stand to deepen their practice by incorporating economic considerations that are largely ignored. PSI is positioned as a bridge between design and economics to serve as a common language and framework.